نظريات ومبادئ لتصميم الألعاب اللغوية الـمحوسبة لمعالجة الصعوبة في تعلّم تصريف الأفعال: نظرية تعلّم اللغة الثانية، مبادئ تصميم وتطوير الوسائط المتعددة، الألعاب اللغوية، الصعوبة النحوية، تصريف الأفعال - ØµØ§Ù„Ø, ØÙ†Ø§Ù†; ØØ³ÙŠÙ†, Ù…ØÙ…Ø¯ (Al-Ḍād Journal, 2018)
This study talks about suitable theories for learning the second language and proposing principles for the design and development of computerized language games to learn Arabic verbs. She also talks about the steps of designing computerized language games to facilitate the process of learning to conduct Arabic verbs to non-native speakers. Chomsky and Piaget’s theory of second language learning and the principles of design and development of multimedia learning by Richard Mayer (2001) and Dickie & Carey’s ADDIE (2014) models were discussed.